A strategic paper for Philippine Fresh Fruits Davao Corporation-Export - Noblefranca, Karl John T.; Digal, Larry N.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2011)
Davao Region is found in the southeastern part of Mindanao-the largest among the islands comprising the Philippine archipelago. Often dubbed as the "Queen City of Mindanao, " it is naturally blessed with fertile lands and mild tropical climate conducive for fresh produce cultivation. Agriculture became its major economic sector. It is to this advantage that the propagation of banana plantations is being credited to. With this, Philippine Fresh Fruits Davao Corporation (PhilFresh) including other local banana exporters, has an edge over other foreign banana exporters in the market as a result of the high quality of fruits being produced. For year 2010, Davao City alone has exported close to 500 million boxes of fresh Cavendish bananas to the global market. This strategic paper aims to enhance the current performance of PhilFresh in its export division focusing primarily on its core product- on product development and market penetration. It is formulated to increase company trade volume translatable to sales; and improve product quality by lessening, as much as possible, eradicate problems. Proposed strategies are aimed at realizing PhilFresh set vision in the next 5 years- to attain an annual export volume of 2 million boxes by consistently providing, healthy, timely, affordable and high quality fresh produce products.
Confidential
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2011.